Captação e geração de energia no pavimento rodoviário com a aplicação de células piezoelétricas - Mota, Bruno Cavalcante (2021)
An increase in the demand for electric energy is emerging in today's society. Faced with the decrease in rainfall in the hydroelectric plant areas and the continental extension of Brazil, there is a need for new alternatives for capturing and generating clean and sustainable energy. Piezoelectricity emerges as an alternative of micro power generation, allowing capturing the vibrations and deformations within pavements. Because the pavement is subjected to traffic of millions of vehicles, it becomes environment suitable for the application of piezoelectric elements, transforming the deformations and vibrations in its layers into electrical energy. Thus, the overall objective of this research is to investigate the use of piezoelectricity as a source of renewable energy applied to pavement. To this end, three methodological steps were performed to verify the amount of power and electrical energy capable of being generated by means of piezoelectric cells: (i) simulation in multiphysics analysis software; (ii) laboratory test with the piezoelectric elements and (iii) estimation of energy production from the simulation in real environment. The results indicate that resistance causes sensitivity in the electric power data. Other factors such as frequency, load, number of cells and spacing affect the amount of power obtained. Regarding the power values for the simulation step, the highest value obtained was 648.8 mW considering load of 10.2 kN, frequency of 20 Hz, and a larger spacing between 4 cells. For the laboratory tests the best electrical response was observed with the use of 8 cells, returning a power of 226.9 mW for 10.2 kN and 20 Hz. The analysis of the results indicated that there is a correlation between the laboratory tests and the computer simulations, and it is possible to obtain up to 76.56 MWh of energy per month for the application of the prototype in ideal conditions on BR-222, in the state of Ceará. Thus, the piezoelectricity was demonstrated as a promising alternative to complement the Brazilian electric matrix and reduce environmental impacts on the natural system.